2015
DOI: 10.1016/j.neuropsychologia.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The role of the amygdala during emotional processing in Huntington's disease: From pre-manifest to late stage disease

Abstract: BackgroundDeficits in emotional processing can be detected in the pre-manifest stage of Huntington's disease and negative emotion recognition has been identified as a predictor of clinical diagnosis. The underlying neuropathological correlates of such deficits are typically established using correlative structural MRI studies. This approach does not take into consideration the impact of disruption to the complex interactions between multiple brain circuits on emotional processing. Therefore, exploration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 80 publications
2
27
0
Order By: Relevance
“…Furthermore, the grey matter volume of left temporo‐parietal junction in healthy participants is positively related to RMET scores (Sato et al, ). Interestingly, we did not identify specific differences in amygdala activity between patients and controls during the RMET as has previously been hypothesized (Mason et al, ), although other findings such as differential activity in the insula and anterior cingulate are in line with previous studies using other facial expression tasks (Dogan et al, ; Labuschagne et al, 2013). The selective deficit on the standard (emotion) version of the RMET provides further support for the likelihood that patients with HD (including premanifest patients) can exhibit a deficit in social cognition per se , rather than their impairments on tasks involving theory of mind being incidental to motor, sensory, or general cognitive impairment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the grey matter volume of left temporo‐parietal junction in healthy participants is positively related to RMET scores (Sato et al, ). Interestingly, we did not identify specific differences in amygdala activity between patients and controls during the RMET as has previously been hypothesized (Mason et al, ), although other findings such as differential activity in the insula and anterior cingulate are in line with previous studies using other facial expression tasks (Dogan et al, ; Labuschagne et al, 2013). The selective deficit on the standard (emotion) version of the RMET provides further support for the likelihood that patients with HD (including premanifest patients) can exhibit a deficit in social cognition per se , rather than their impairments on tasks involving theory of mind being incidental to motor, sensory, or general cognitive impairment.…”
Section: Discussionsupporting
confidence: 88%
“…Most early studies of social cognition in HD explored emotion recognition, and many highlighted a disproportionate deficit in the recognition of disgusted facial expressions (Gray, Young, Barker, Curtis, & Gibson, ; Montagne et al, ; Sprengelmeyer et al, ), although later studies revealed that deficits are common with other negative emotions such as anger (Henley et al, ; Mason et al, ). Interestingly, correlations between emotion expression and recognition have been highlighted in this patient population (Trinkler, Cleret de Langavant, & Bachoud‐Lévi, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the pattern of hostility exhibited by HD monkeys is due to alterations in amygdala activity. Recent studies in HD patients have shown decreased amygdala activity during emotional tasks lending support for this hypothesis (Mason et al, 2015; Van den Stock, et al, 2015). Additionally, HD patients have also been shown to exhibit lower fear and higher anger ratings of fearful pictures as compared to healthy controls (Eddy, et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
“…The optic chiasm is not expected to be pathologically involved in the disease progression, but may undergo changes in volume due to the atrophy of surrounding tissues. Measurements of the volume of the third ventricle by transcranial sonography have shown that it is significantly larger in HD patients than HCs 38. Finally, the EBM predicts the posterior insula and basal forebrain as late‐stage biomarkers.…”
Section: Discussionmentioning
confidence: 97%